1. Select positive integers a and b such that a^3-(a-1)^3=(b^2)+(b-1)^2 starting with {a,b}={1,1}, numbering successive solutions {a
1,b
1}...{a
n,b
n}
2. Select positive integers x and y such that 3x^2-2y^2=1 starting with {x,y}={1,1}, again numbering successive solutions {x1,y1}...{xn,yn}
3. Let n exceed 1. Let {xn-1, yn-1}={X,Y}; let {an, bn}={A,B}.
Prove that X+Y=2(B-A).
(In reply to
Outline Solution (spoiler) by Harry)
Very nice! and quite different from my own method, which I have submitted as a draft solution, in case you are interested.
Solution now posted, since I did not receive any comments on the draft.
Edited on June 6, 2011, 8:54 am
|
Posted by broll
on 2011-05-28 09:48:04 |